1987
DOI: 10.1159/000124866
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Photoperiod and Morphine on Plasma Prolactin Concentrations and Thyrotropin-Releasing Hormone Secretion in the Ewe

Abstract: This study investigated the effects of daily photoperiod length and morphine on thyrotropin-releasing hormone (TRH) and prolactin secretion in sheep. Two groups of adult ewes were kept under either 16hL:8 h D or 8 h L:16 h D photoperiods for approximately 60 days. Then the photoperiods were reversed and approximately 60 days later push-pull cannulae were implanted into the hypothalamic stalk-median eminence. After a 7-day recovery period, the ewes were subjected to hypothalamic perfusion and blood was collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
3
0

Year Published

1989
1989
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
2
3
0
Order By: Relevance
“…Furthermore, protein expression of ATP synthase and MFF as well as ATP synthase activity was highest in the moderate photoperiod control group. HE staining showed that the HG of striped dwarf hamsters contained a large number of secretory cells of species-specific morphotypes, indicating a possible secretory function, as has been shown in previous studies on female striped dwarf hamsters, golden hamsters, sheep, and other mammals [56][57][58]. Here, we found that after 10 weeks of different light treatment, HG weight in the short and long photoperiod groups was lower than that in the moderate photoperiod group.…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, protein expression of ATP synthase and MFF as well as ATP synthase activity was highest in the moderate photoperiod control group. HE staining showed that the HG of striped dwarf hamsters contained a large number of secretory cells of species-specific morphotypes, indicating a possible secretory function, as has been shown in previous studies on female striped dwarf hamsters, golden hamsters, sheep, and other mammals [56][57][58]. Here, we found that after 10 weeks of different light treatment, HG weight in the short and long photoperiod groups was lower than that in the moderate photoperiod group.…”
Section: Discussionsupporting
confidence: 86%
“…function, as seen in previous studies on rats, sheep, and other mammals (Leshin and Jackson, 1987;Jimenez-Jorge et al, 2007). Similarly, ultrastructural observation of the HG also identified many lipid droplets in the cells, again indicating that the HG may have a secretory function.…”
Section: Photoperiod Changes In Morphology and Hormone Synthesis In Hgsupporting
confidence: 84%
“…However, Arita and Porter [2] concluded that the decrease in dopamine secretion in duced by morphine in the rat hypothalamus was not suffi cient to account for all of the observed increase in pituitary prolactin secretion. In the adult ewe, morphine infusion was associated with elevated plasma prolactin concentrations and also an increase in TRH secretion from the median emi nence [16]. Previous studies have demonstrated that TRH.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, acute administration of morphine is associated with fetal and maternal hyperprolactinaemia. Although the endogenous opioids do not appear to mediate basal prolactin secretion in the fetus, they may have a role in the control of prolactin release in the pregnant ewe during late gestation.There is extensive evidence that administration of opioid peptides or opiates can stimulate prolactin secretion in a variety of species including rat, man and sheep [7,16, 24, 25, 30]. As opioid peptides and opiates are unable to stimu late pituitary cells in culture to release prolactin directly, it has been argued that these compounds act via the hypotha lamus to stimulate pituitary prolactin secretion [4, 24].…”
mentioning
confidence: 99%
See 1 more Smart Citation